Peculiarities of the course of gestation in women with a history of reproductive loss - V. H. Siusiuka; N. M. Soloviova (Zaporozhye State Medical University, 2024)
Aim. Тo assess the frequency of extragenital pathology, features of obstetric and gynecological history and the course of pregnancy in women with a history of reproductive loss. Materials and methods. The study was conducted on the basis of the Municipal non-profit enterprise "Maternity house No. 9" of the Zaporizhzhia City Council with the involvement of 75 pregnant women with one reproductive loss in history. The control group consisted of 30 women without a history of reproductive loss. Women who had reproductive losses were divided into 2 groups. Group I (main group) includes 38 pregnant women who registered for pregnancy and began their participation in this study after the start of a full-scale war on the territory of Ukraine. II (comparison) group included 37 women who were registered for pregnancy before the start of the full-scale war. It should be noted that 17 pregnant women (44.7 %) had the status of an internally displaced person. The average age of women in group I was 30.10 ± 5.86 years, in group II - 28.80 ± 6.07 years, and 26.50 ± 4.95 years in the control group. The anamnesis data and features of the course of gestation were studied in all patients. Management of pregnancy and childbirth of women was carried out in accordance with the current Orders of the Ministry of Health of Ukraine. Variational and statistical processing of the results was carried out using the Statistica 13 program. Results. According to the results of the study, it was established that the frequency of extragenital pathology in women with one reproductive loss was higher, compared to women who had no such experience. Diseases of the cardiovascular and urinary systems occupy a leading place in this category of women. According to obstetric and gynecological anamnesis, a significant predominance among women of I and II groups of diseases of the reproductive system, compared to women of the control group, was established. Also, in the corresponding groups, a high frequency of miscarriage was established both in the period up to 12 weeks (28.95 % in the I group, 43.2 % in the II group against 6.67 % in the control group), and in the period of 12-22 weeks (34.20 % in the I group, 29.73 % in the II group vs. 13.33 % in the control group). Conclusions. Based on the conducted analysis, a high frequency of pregnancy complications was established for pregnant women who had a history of one reproductive loss. This contingent of women also has a high frequency of extragenital and gynecological concomitant pathology. Such results make it possible to assume a connection between the presence of one reproductive loss in women in the anamnesis and gestational complications of the next pregnancy.